In situ atomic-scale studies of the formation of epitaxial Pt nanocrystals on monolayer molybdenum disulfide - Wang, S; Sawada, H; Chen, Q; Han, G; Allen, C; Kirkland, A; Warner, J (American Chemical Society, 2017)
Pt-nanocrystal:MoS2 hybrid materials have promising catalytic properties for hydrogen evolution, and understanding their detailed structures at the atomic scale is crucial to further development. Here, we use an in situ heating holder in an aberration-corrected transmission electron microscope to study the formation of Pt nanocrystals directly on the surface of monolayer MoS2 from a precursor on heating to 800 °C. Isolated single Pt atoms and small nanoclusters are observed after in situ heating, with two types of preferential alignment between the Pt nanocrystals and the underlying monolayer MoS2. Strain effects and thickness variations of the ultrasmall Pt nanocrystal supported on MoS2 are studied, revealing that single atomic planes are formed from a nonlayered face-centered cubic bulk Pt configuration with a lattice expansion of 7-10% compared to that of bulk Pt. The Pt nanocrystals are surrounded by an amorphous carbon layer and in some cases have etched the local surrounding MoS2 material after heating. Electron beam irradiation also initiates Pt nanocrystal etching of the local MoS2, and we study this process in real time at atomic resolution. These results show that the presence of carbon around the Pt nanocrystals does not affect their epitaxial relationship with the MoS2 lattice. Single Pt atoms within the carbon layer are also immobilized at high temperature. These results provide important insights into the formation of Pt:MoS2 hybrid materials.